IMPLEMENTASI KONSTITUSI TERHADAP PERLINDUNGAN HAK ASASI MANUSIA DALAM PRESPEKTIF HUKUM TATA NEGARA - Harry Gusti Atmaja; Iftitah Rizkya Cahyani; Lutfiah Ananda Nasution; Pema Suryanta Bintang; Suntya Indah Lestari; Tamaulina Br. Sembiring (Bajang Institute, 2025)
Human rights are basic rights that are very important and inherent in every person from birth. In Indonesia, the 1945 Constitution (UUD 1945) serves as the protector of human rights. The purpose of the legal system in Indonesia is to safeguard and defend these rights. This thesis will discuss how the Indonesian legal system protects human rights by looking at the application of the constitution in everyday democratic practice. We will review the basic laws relating to human rights, the mechanisms for protecting human rights in the Indonesian legal system, as well as the challenges faced in their implementation. This analysis shows that the Indonesian constitution provides a strong legal basis for protecting human rights, especially in the context of freedom of democracy in the country, from the perspective of the people